Market-driven production of biospecimens and the role of NHS hospital-led biobanks - Timmons, Stephen; Vezyridis, Paraskevas (Blackwell Publishing, 2017)
Biobanks are vital for biospecimen production in research, despite the regulatory, recruitment and commercial difficulties they face. We conducted interviews with clinicians, researchers, volunteers who recruit biobank participants, regulators and NHS managers about the integration of a biobank into an NHS hospital. We show that medical waste collected for biomedical research acquires its socio-ethical and economic value from the level of integration (both technologically and organisationally) of the biobank into the NHS hospital. There is extensive investment in a range of intellectual and commercial relationships and labour among stakeholders involved in the production of biospecimens. It is not only the boundaries of research, clinical care and commercialisation of biospecimens that blur but also those of volunteerism and citizenship. Hospital-led biobanks provide an opportunity to study the intertwining of biomedical innovation and healthcare.